Impact of food quality influencing the behavioral intention on customer satisfaction: food outlet owner vs customer/ Soffian Mohd Ibrahim - Mohd Ibrahim, Soffian (2015)
Food quality is the quality characteristics of food that is acceptable to consumers. This includes external factors as appearance (size, shape, colour, gloss, and consistency), texture, and flavour; factors such as federal grade standards (e.g. of eggs) and internal (chemical, physical, microbial), (wikipedia, 2016). The objectives of this study are to identify the determinants of the food quality at food outlet, to study how do these determinants affect customer behavioral intention and to investigate the effect of behavioral intention towards customer satisfaction at food outlet. The method used in this study are realibility analysis, descriptive analysis (mean, frequency), regression analysis and pearson correlation analysis. The results of this study shows that menus item variety of the food does not really affect behavioral intention of customer’s satisfaction because the customer prefer the tastiness of the food. Therefore, there have another factor that influence customer’s satisfaction towards food outlets.